Creative Economy Development Challenges for Halal Tourism: A Study in Madura, Indonesia - Kamiluddin; Zulfikar Hasan (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2023)
Indonesia is a country that has potential in the tourism sector. In the context of creative economy-based tourism, Sumenep, one of the districts in Madura, has the potential to be optimally developed. However, issues such as the production of sharia-compliant products, raw materials and product marketing have become challenges for creative economy entrepreneurs in this region. This study was conducted to closely examine the development of the creative economy for halal tourism in Sumenep by focusing on the real challenges faced by creative economy entrepreneurs, especially in the handicraft sector. The data collected was then analyzed using thematic analysis. The analysis resulted in three main findings. First, implementing a creative economic development concept for halal tourism must be in line with the Halal Tourism Development Development Acceleration Team (TP3H) criteria. Second, nine challenges faced by creative economy entrepreneurs in Sumenep are the quality and quantity of human resources, capital, sharia-compliant products, competitors from outside the region, raw materials, marketing strategies, information and technology infrastructure, and Government policy. Competitors from outside the area are the main challenge faced by Sumenep's creative economy entrepreneurs. Third, training strategies, venture capital assistance, product innovation, marketing systems development, business partnerships, and the establishment of consulting and development centres could be implemented to deal with these challenges, with the cooperation of entrepreneurs and the government